(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The article examines the scientific research activities conducted in higher education institutions, the modernization of teaching methodologies, as well as factors such as inter-university cooperation and the implementation of innovations. It also highlights the role of these processes in enhancing the scientific capacity of universities and improving the overall quality of education.